Diet‐induced pigmented purpuric dermatosis. (10th April 2013) - Weiß, Katharina T.; Karrer, Sigrid; Landthaler, Michael; Babilas, Philipp; Schreml, Stephan
Abstract Pigmented purpuric dermatoses (PPD) are chronic and relapsing disorders characterised by a localised or generalised purpuric rash. Even though the clinical presentation of PPD subtypes varies, they have a similar histopathology. The aetiology is largely unknown, but trigger factors, such as drugs, infections and systemic illnesses have been described. To our knowledge, this is the only case showing widespread PPD lesions not only induced but also rapidly provoked by dietary factors, namely Coca Cola and apple‐cherry fruit spritzer.